2002
DOI: 10.2188/jea.12.1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sources of Nutrient Consumption in a Rural Japanese Population.

Abstract: We determined the sources of nutrient intake of 59 men and 60 women in two rural towns in the Miyagi Prefecture, a northeastern part of Japan. Four 3-day food records were collected in four seasons within a year. The total dishes and recipes were classified into 197 items. Their percent contributions to the total population consumption of energy and 14 nutrients were calculated as the sum of the nutrient intake contributed by a given dish or recipe divided by the total nutrient intake from all the items.Rice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…This is a key finding that may have important public health implications, as public health workers often give nutritional education based on the nutritional content of common dishes and recipes (8). In this context, our findings regarding differences in dietary habits according to age provide valuable insight.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…This is a key finding that may have important public health implications, as public health workers often give nutritional education based on the nutritional content of common dishes and recipes (8). In this context, our findings regarding differences in dietary habits according to age provide valuable insight.…”
Section: Discussionmentioning
confidence: 65%
“…A previous study using data collected in 1996-1997 reported that miso soup and Japanese pickles are the top two contributors of dietary sodium, accounting for 17.1% and 12.4% of total sodium intake, respectively, among 197 common Japanese dishes (8). Japanese pickles include pickled cucumber (3.6%), pickled radish (2.9%), pickled plum (2.8%), pickled vegetables (1.3%), pickled eggplant (1.0%) and pickled Chinese cabbage (0.8%).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although different studies have characterized within-and between-person variance for energy and nutrient intakes in adults 10,11 very little information is available for children 12,13 , especially in Brazil. In addition, most studies of the child population are usually held in public health institutions and at nursery schools 14,15,16,17,18 and few population-based studies have been conducted in recent years 19,20,21,22 .…”
Section: Introductionmentioning
confidence: 99%